Sorry sir, the previous question was wrong. the real question goes like this:

Asked by Sthitaprajna Mishra | 24th Sep, 2013, 08:20: AM

Expert Answer:

1/(1 + x + y-1) + 1/(1 + y + z-1) + 1/(1 + z + x-1)
1/(1 + x + y-1) + 1/(1 + y + xy) + 1/(1 + 1/xy + 1/x)
(since xyz = 1)
= 1/(1 + x + 1/y) + 1/(1 + y + xy) + 1/(1 + 1/xy + 1/x)
= y/(y + xy + 1) + 1/(y + xy + 1) + xy/(xy + 1 + y)
= (y + 1 + xy)/(y + xy + 1)
= 1
 
Hence, proved.

Answered by  | 24th Sep, 2013, 09:00: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.